Enlarging head size as the only presentation of Salmonella Typhimurium brain abscess in an infant: a short report. (June 2014) - Mohindra, Sandeep; Savardekar, Amey; Tripathi, Manjul; Raj, Atul
Abstract The authors describe a 5-month-old male harbouring a giant Salmonella Typhimurium cerebral abscess who presented with progressively enlarging head size, without any features of septicemia. The report details the radiological findings, differential diagnoses and management problems regarding the index case.